2013
DOI: 10.5539/ep.v3n1p82
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Climate Change Perceptions: A Case Study in Brazilian Biomes

Abstract: Based on the assumption that vulnerability is socially constructed, and may thus change according to transformations in human action, it appears necessary to consider the issue at the core of studies on the social aspects of Climate Change (CC), risk level and disaster prevention. The social nature of vulnerability is determined by elements such as poverty, inequality, exclusion and access to sanitation, water, food and education among other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…These findings are in concordance with other studies that have also suggested that if farmers are not aware that they are vulnerable to the effects of climate change they will be less likely to respond e.g. in rural communities in Brazil (da Silva-Rosa et al 2014 [31]).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in concordance with other studies that have also suggested that if farmers are not aware that they are vulnerable to the effects of climate change they will be less likely to respond e.g. in rural communities in Brazil (da Silva-Rosa et al 2014 [31]).…”
Section: Discussionsupporting
confidence: 92%
“…The coping mechanisms that were mentioned as being already used by farmers were the use of land units, intercropping, and crop rotation, but farmers did not consider that as changing their practices and did not plan to change practices despite reductions in yields. These findings are in concordance with other studies that have also suggested that if farmers are not aware that they are vulnerable to the effects of climate change they will be less likely to respond e.g., in rural communities in Brazil [32].…”
Section: Discussionsupporting
confidence: 92%